2008
DOI: 10.1161/hypertensionaha.107.103523
|View full text |Cite
|
Sign up to set email alerts
|

Acute Blood Pressure Lowering, Vasoprotective, and Antiplatelet Properties of Dietary Nitrate via Bioconversion to Nitrite

Abstract: Abstract-Diets rich in fruits and vegetables reduce blood pressure (BP) and the risk of adverse cardiovascular events.However, the mechanisms of this effect have not been elucidated. Certain vegetables possess a high nitrate content, and we hypothesized that this might represent a source of vasoprotective nitric oxide via bioactivation. In healthy volunteers, approximately 3 hours after ingestion of a dietary nitrate load (beetroot juice 500 mL), BP was substantially reduced (⌬ max Ϫ10.4/8 mm Hg); an effect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

82
975
9
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 940 publications
(1,126 citation statements)
references
References 51 publications
82
975
9
14
Order By: Relevance
“…Consistent with previous investigations, plasma nitrate and nitrite, and exhaled NO concentrations were significantly elevated following dietary nitrate supplementation [1,2,5,8,55,22,39,38], signifying an increase in the 'substrates' available for NO generation via the nitrate-nitrite-NO pathway [11]. Peak plasma nitrite concentration was 602 % higher in BRJ versus PLA, similar to Arnold et al [38] (775 %) (~ 7 mmol nitrate), but considerably greater than reported by Muggeridge et al [22] (134 %) (~ 5 mmol nitrate) and Vanhatalo et al [8] (150 %) (~ 9.3 mmol).…”
Section: Plasma Nitrate Nitrite and Exhaled Nosupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous investigations, plasma nitrate and nitrite, and exhaled NO concentrations were significantly elevated following dietary nitrate supplementation [1,2,5,8,55,22,39,38], signifying an increase in the 'substrates' available for NO generation via the nitrate-nitrite-NO pathway [11]. Peak plasma nitrite concentration was 602 % higher in BRJ versus PLA, similar to Arnold et al [38] (775 %) (~ 7 mmol nitrate), but considerably greater than reported by Muggeridge et al [22] (134 %) (~ 5 mmol nitrate) and Vanhatalo et al [8] (150 %) (~ 9.3 mmol).…”
Section: Plasma Nitrate Nitrite and Exhaled Nosupporting
confidence: 91%
“…These include, but are not restricted to: lower blood pressure [1][2][3], reduced O2 consumption (V O2) during steady-state exercise [4][5][6], attenuated muscle metabolic perturbations [7,8], and enhanced muscle force production [9,10]. These effects are not directly attributable to the nitrate anion, which is relatively inert [11].…”
Section: Introductionmentioning
confidence: 99%
“…Renal NO X excretion is less in sunitinib‐treated rats than in controls,11, 16 which is indicative of reduced NO formation and availability 29. Oral nitrate supplementation has been shown to lower arterial pressure in humans30 and in rats 21, 22. Therefore, we tested whether oral nitrate supplementation lowers arterial pressure in sunitinib‐treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Of those utilising a similar BR source, in one or two repeated tests there is an apparent split between those exhibiting high relative yield [12][13][14] and those finding significantly lower yield [3,11]. In these examples, volume of NO 3 -administration does not appear to be the cause of the discrepancy, neither does this appear to be methodological (since all studies essentially use ozonebased chemiluminescence to measure plasma NO metabolites). ]…”
Section: Nitrate (No 3 -) Sourcementioning
confidence: 99%
“…Its application to modulate physiology and alleviate cardiovascular dysfunction shows particular promise in certain clinical conditions and patient cohorts, including reduction of mean arterial pressure in hypertension [1,2], effective quiescencing of platelet activation/aggregation [3], and reduce risk in conditions where tissue ischemia prevails [4]. However, it is the potential of oral NO 3 -to modify exercise/performance via elevation of plasma nitrite concentration ([NO 2 -]) that has been applied across a range of human test systems, from the effects of walking distance in a sedentary population [5] to enhancing performance in elite athletes [6].…”
Section: Introductionmentioning
confidence: 99%